Dekonstruksi Makna Peusijuek dalam Fenomena Sosial Masyarakat Aceh Pada Kajian Jaques Derida - Risma Dewi Portuna Putri; Masrizal Masrizal; Fajrul Ali; Zukhra Sanjaya; Raudhatun Nur; Sa'i Sa'i (Prodi Sosiologi FISIP Universitas Teuku Umar, 2023)
The socio-cultural phenomenon of peusijuek in Acehnese society has developed from time to time. The deconstruction of peusijuek culture in line with the meanings contained in it is a cultural text that needs to be re-understood to see other meanings contained in the peusijuek tradition itself. Deconstruction in this case by the author is a dismantling of the culture and meaning of the peusijuk by reading the original life. This research is a study of the deconstruction that takes place on the meaning of peusijuek. The library research technique was used to carry out the research for this study. According to the findings of this study, the tradition of peusijuek has developed differently in Aceh ever since Islam was introduced there. Following this, the Peusijuek tradition was altered by the incorporation of components of Islamic teachings within it. These components included prayers of salvation, shalawat, and other Islamic teachings. The meaning of the peusijuek tradition undergoes changes that are adapted to what type of peusijuek is carried out which is also followed by changes in these meanings. A culture that undergoes commodification will give birth to a new meaning that will lead to the deconstruction of the meaning of an element.